Chemical tools to characterize the coordination chemistry of radionuclides for radiopharmaceutical applications - Boros, Eszter; Comba, Peter; Engle, Jonathan W.; Harriswangler, Charlene; Lapi, Suzanne E.; Lewis, Jason S.; Mastroianni, Simona; Mirica, Liviu M.; Platas-Iglesias, Carlos; Ramogida, Caterina F.; Tripier, Raphaël; Tosato, Marianna (Chemical reviews, 2025)
During the past decade, the advancement and approval of novel radiopharmaceuticals for clinical application has led to a resurgence of the field of radiochemistry and specifically the coordination chemistry of radionuclides. In addition to well established radionuclides, short-lived radioisotopes of other elements are becoming accessible using new isotope production methods, necessitating the development of coordination chemistry compatible with the aqueous chemistry of such elements under tracer level conditions. As radiochemistry with radioactive metal ions relevant for radiopharmaceuticals is conducted at the nano- to picomole scale, conventional chemical characterization techniques can generally not be applied. Therefore, careful consideration and interfacing of tracer-level compatible techniques and macroscopic characterization methods is required. This Review provides an in-depth survey of common, contemporary characterization strategies for the coordination chemistry of radionuclides, including case studies to demonstrate context and relevance for the prospective development of clinically translatable radiopharmaceuticals.